Empowering ESL teachers’ professional development through digital literacy - Suppiah, Gunavathy; Ong, Chuin Yin; Othman, Moomala; Ismail, Lilliati; Aralas, Dalia (Human Resource Management Academic Research Society, 2018)
With todays technology, teachers need to have digital literacy. It is a key requirement for teachers’ professional growth in order to be functional in today's teaching profession. Thus it is important for teachers to have a digital mindset. Teachers need to be techno savvy and use available online interactive platforms in sharing their teaching practice. Advancement in technology provides opportunities for the learning processes as one is able to access various forms of information as well as share one’s ideas through the use of multi-modal communication style. This paper aims to overlook at ICT as not only as a teaching tool but as a platform to exchange knowledge among teachers or instructors. Teachers can then creatively produce and contribute resources to be shared with others online. Raising awareness among teachers of the importance of digital literacy, will foster teachers' continuous and lifelong professional development.